Elucidation of rGO incorporation on structural, morphological and optical properties of rGO/ZnO nanocomposites for flexible humidity sensor applications / A. Shamsul Rahimi A. Subki ... [et al.] - A. Subki, A. Shamsul Rahimi; Mamat, Mohamad Hafiz Mamat; Mahmood, Mohamad Rusop; Kamaruzaman, Dayana; Abdullah, Mohd Hanapiah; Mohamed Zahid, Musa (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2022)
The effect on structural, morphological and optical characteristics towards humidity sensing capability was elucidated as humidity-sensitive sensing material that is made by composting zinc oxide nanostructured powder (ZN) nanoparticles with varying capacities of reduced graphene oxide (rGO). The ZN was successfully synthesized through the ultrasonicated solution immersion technique and the rGO/ZN (rZN) nanocomposite sensing material was spread on cellulose substrates employing a simple brush printing technique. XRD, FESEM and UV–Vis Diffuse Reflectance Spectroscopy were utilized to examine the morphological and optical properties of the pristine ZN and rZN nanocomposites. As per the FESEM assessment, ZN nanoparticles with variable sizes were evenly distributed, adhered to, and irregularly positioned on filter paper cellulose fibres. The average reflectance in the visible region declined substantially as the rGO content increased. According to the estimated Urbach energy, the defects in the sensing materials increased as the rGO content increased. The humidity response capability of the nanocomposites exhibits a significant reliance on the quantity of rGO integrated, with the maximum humidity sensitivity achieved for the 1.0 wt.% rGO dosage. At a high operating temperature (85°C), the humidity sensor based on rZN-1.0% nanocomposite exhibits an amplified humidity sensing response current value. These outcomes indicate that rZN nanocomposites have the potential to operate as a humidity-sensitive sensing material with great sensitivity.